(3QSGdI aj GdNdd GdhGbY aj GdUdGIs - (3GdHQZGfj, ESMGb Hf eMeO Hf GdTgjO GdKGdKs ((3HNW eDdagGs)
(3ChdgG (B:s
(3HSe Gddg(B...(3bGd(B...(3GdQcf GdQGHY aj GdJhGHY ajg aUhd GdaUd GdChd aj GdNdd GdhGbY aj GdUdGI(B...s
(3BNQgG (B:s
...(3JeJ eSCdI UdGI GdeSGaQ HYhf Gddg Gdedc GdYdGe(B...(3hfSCd Gdedc GdefGf Cf jef YdjfG HGdJhajb(B...(3hdG bhI EdG HGddg GdYdj GdYXje (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis